Utilisation of Information and Communication Technology for Environmental Sustainability: A Global Perspective - Cedric Owuru; Jude Odiakaosa Osakwe; Samuel Akinsola (Universitas Bina Darma, 2021)
There has been a rapid development of Information and Communication Technologies (ICTs) globally, and ICT have been used as a tool to attain environment sustainability all over the world. There are diverse environmental challenges faced by developing countries such as ecosystem deterioration, pollution, resource depletion, loss of biodiversity and climate change and the management of above problems is difficult because they involve multiple actors and its occurrence is over time and space. Environmental Scientists have raised concerns on how these environmental challenges can be tackled bringing into lamplight, how ICT and environmental science research can be used to wedge these challenges in developing countries. The study is exploratory and employed the use of survey questionnaires as an instrument to collect data. Findings revealed that a lot needs to be done for ICT to be effectively used in the environment, factors such as inadequate facilities, problem of acceptance and adaptation of technology, lack of awareness and illiteracy, mismanagement, lack of technical know-how and unstable internet service are challenges that should be looked at to leverage ICT in the environment. The study also noted the fact that ICT has affected the society and its environments in other negative ways such as the production of unwanted by-products called pollution and depletion of natural resources.